Analisis Bantuan Keuangan Khusus Terhadap Peningkatan Infrastruktur Masyarakat Desa Sebagai Indikator Peningkatann Kesejahteraan Di Kabupaten Jombang - Mohammad Hari Prasetyo; Muhammad Mudjib Musta‟in; Supriyanto (Universitas Darul Ulum, 2018)
Special Financial Assistance (BKK) to villages in the Field of Facilities and Infrastructure is Special financial assistance given to build infrastructure at the village or cross-village level. who are not included in the Village Fund proposal (DD) and Village Fund Allocation (ADD). In the study, it tried to find answers to the problems of the existence or absence of the BKK relationship to improving welfare through infrastructure development with welfare indicators through the 2013-2017 GRDP-ADHK. With a survey research model and simple quantitative regression descriptive linear regression analysis, it was found that there was no influence between BKK and welfare, with the influence of 0.402. This shows that the influence of Special Financial Aid is in a weak position on the value of welfare. Obstacles in infrastructure development using Special Financial Assistance are the lack of supervision conducted by the community in the implementation of development, weather and place, the price of materials and unaccountable reporting.